Laparoscopic suture repair for perforated peptic ulcer disease: a meta-review and trial sequential analysis - Panin, S. I.; Nechay, T. V.; Sazhin, I. V.; Melnikov-Makarchuk, K. Yu.; Sazhin, A. V.; Puzikova, A. V.; Akinchits, A. N.; Bykov, A. V. (Frontiers in Surgery, 2025)
BackgroundThe number of systematic reviews (SRs) and meta-analyses in surgery is growing exponentially. Meta-epidemiology, as a form of evidence synthesis, allows for the pooling of data and assessment of the diversity present in multiple and overlapping SRs.Aim of the researchThis study aimed to summarize evidence from systematic reviews of randomized controlled trials and reanalyze outcome data on laparoscopic suture repair of perforated peptic ulcers using trial sequential analysis (TSA).Materials and methodsThe Cochrane Library, PubMed, Embase, CINAHL, eLibrary, and ClinicalTrials.gov were searched before 1 June 2024. A meta-epidemiological approach and TSA were used.ResultsIn total, 16 relevant Cochrane and non-Cochrane SRs that addressed laparoscopic repair of perforated peptic ulcers (PPUs) were identified and critically appraised. Three overlapping reviews of RCTs met the inclusion criteria. Their pooled results showed a lower postoperative pain score after laparoscopic repair compared with open closure on postoperative day 1 as the only significant outcome. There were no significant differences in other clinical outcomes. The re-analyses of meta-analytic findings and adjustments of sample size by TSA confirmed that laparoscopic repair was associated with less postoperative pain [100% of the diversity-adjusted required information size (DARIS) was reached]. The calculated DARIS for operative time and hospital stay were 40.1% and 14.6%, respectively, and the TSA showed neither significant benefit nor harm of laparoscopic surgery in the attained information size in the meta-analysis. Further trials with regard to mortality, surgical site infection, and intra-abdominal abscess are not very promising because the DARIS did not exceed 5% after combining the results of eight RCTs.ConclusionSummarization of evidence from systematic reviews and reanalysis using TSA confirmed sufficient evidence for only one outcome, namely, that laparoscopic suture repair of PPUs is accompanied by lower pain scores at 24–72 h. Regarding the issues of postoperative complications and mortality, achieving DARIS through additional studies seems unpromising.